The effect of telephone-based interpersonal psychotherapy for the treatment of postpartum depression: study protocol for a randomized controlled trial - Dennis Cindy-Lee; Ravitz Paula; Grigoriadis Sophie; Jovellanos Melissa; Hodnett Ellen; Ross Lori; Zupancic John (Trials, 2012)
Abstract Background Substantial data indicate potential health consequences of untreated postpartum depression (PPD) on the mother, infant, and family. Studies have evaluated interpersonal psychotherapy (IPT) as treatment for PPD; however, the results are questionable due to methodological limitations. A comprehensive review of maternal treatment preferences suggests that mothers favor ‘talking therapy’ as a form of PPD treatment. Unfortunately, IPT is not widely available, especially in rural and remote areas. To improve access to care, telepsychiatry has been introduced, including the provision of therapy via the telephone. Methods/Design The purpose of this randomized controlled trial is to evaluate the effect of telephone-based IPT on the treatment of PPD. Stratification is based on self-reported history of depression and province. The target sample is 240 women. Currently, women from across Canada between 2 and 24 weeks postpartum are able to either self-identify as depressed and refer themselves to the trial or they may be referred by a health professional based on a score >12 on the Edinburgh Postnatal Depression Scale (EPDS). Following contact by the trial coordinator, a detailed study explanation is provided. Women who fulfill the eligibility criteria (including a positive diagnostic assessment for major depression) and consent to participate are randomized to either the control group (standard postpartum care) or intervention group (standard postpartum care plus 12 telephone-based IPT sessions within 12 to 16 weeks, provided by trained nurses). Blinded research nurses telephone participants at 12, 24, and 36 weeks post-randomization to assess for PPD and other outcomes including depressive symptomatology, anxiety, couple adjustment, attachment, and health service utilization. Results from this ongoing trial will: (1) develop the body of knowledge concerning the effect of telephone-based IPT as a treatment option for PPD; (2) advance our understanding of training nurses to deliver IPT; (3) provide an economic evaluation of an IPT intervention; (4) investigate the utility of the EPDS in general clinical practice to identify depressed mothers; and (5) present valuable information regarding PPD, along with associated couple adjustment, co-morbid anxiety and self-reported attachment among a mixed rural and urban Canadian population. Trial registration Current Controlled Trials Ltd. ISRCTN88987377.